2020
DOI: 10.1101/2020.04.12.20062943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence, clinical outcomes, and transmission dynamics of hospitalized 2019 coronavirus disease among 9,596,321 individuals residing in California and Washington, United States: a prospective cohort study

Abstract: Background:The United States is now the country reporting the highest number of 2019 coronavirus disease (COVID-19) cases and deaths. However, little is known about the epidemiology and burden of severe COVID-19 to inform planning within healthcare systems and modeling of intervention impact. Methods:We assessed incidence, duration of hospitalization, and clinical outcomes of acute COVID-19 inpatient admissions in a prospectively-followed cohort of 9,596,321 individuals enrolled in comprehensive, integrated he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
6
27
6
Order By: Relevance
“…Moreover, in contrast to our study, the US and Canadian estimates were not adjusted for the sensitivity of RT-PCR assays and health seeking behaviors, and thus may be underestimated. Our estimated hospitalization rate for a 4-month COVID-19 outbreak was much higher than that for a 3-6-month COVID-19 outbreak in the US and Québec (370 vs. 50-114 per 100,000 persons) [27][28][29][30] . We estimated that 76% of medically-attended cases were hospitalized in Wuhan, while only 18% were hospitalized in the US 30 .…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, in contrast to our study, the US and Canadian estimates were not adjusted for the sensitivity of RT-PCR assays and health seeking behaviors, and thus may be underestimated. Our estimated hospitalization rate for a 4-month COVID-19 outbreak was much higher than that for a 3-6-month COVID-19 outbreak in the US and Québec (370 vs. 50-114 per 100,000 persons) [27][28][29][30] . We estimated that 76% of medically-attended cases were hospitalized in Wuhan, while only 18% were hospitalized in the US 30 .…”
Section: Discussioncontrasting
confidence: 56%
“…Our estimated hospitalization rate for a four-month COVID-19 outbreak was much higher than that for a three-to-six-month COVID-19 outbreak in the US and Qué bec (370 vs. 47-114 per 100,000 persons) 27,28,29,30 . We estimated that 76% of medicallyattended cases were hospitalized in Wuhan, while only 18% were hospitalized in the US 30 . The difference between these estimates could be explained by the potential different clinical thresholds for hospitalization.…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies have been published after our search dates which provide additional LoS estimates from outside of China. A study of 5700 patients from hospitals in the New York area reported comparable estimates for total LoS (median 4.5; IQR 2.4-8.1) [51]; however, studies from Northern Italy [52], Japan [53], and California and Washington [50] reported longer estimates of LoS. Therefore, the total LoS outside of China may in fact be longer than what we concluded.…”
Section: Limitations and Biasescontrasting
confidence: 41%
“…Two studies [27,38] were included in the review which reported LoS by age, and they both found longer LoS associated with older age groups. In addition, two studies of LoS from the USA which were published after the search dates also reported a trend for longer LoS in older age groups [50,51]. Studies also reported LoS by disease severity; however, the definitions of disease severity were not consistent across studies, so we did not summarise by this.…”
Section: Summary Of Findingsmentioning
confidence: 98%